IDENTIIFKASI PROTEIN IMUNOGENIK CHLAMYDIA PNEUMONIAE TERHADAP SERUM PENDERITA INFARK MIOARD AKUT - Murwani, Sri; Hidayati, Dwi Yuni Nur (Jurnal Kedokteran Brawijaya, 2007)
Chlamydia pneumoniae is human respiratory tract pathogen and recently investigated as pathogen causingatherosclerosis and acute myocardial infarction (AMI). This research was carrier out to detect proteinpattern of C. pneumoniae, and to study it relation to AMI throughdetection of immunogenic protein. Design research  was laboratory observational and analyzed descriptively. The subject was C. pneumoniae. Protein pattern the bacteria was detected by electrophoresis method, and to detect the immunogenic protein was done immunoblotting. Serum was obtained from AMI patients in Saiful Anwar and Lavallette hospitals.  The result showed, protein pattern C. pneumoniae wasprotein with molecular weight 117, 107, 97, 91, 86, 61, 58, 52, 46, 44, 34, 23, 19, 9, 5, 4 kDa. Immunogenic proteins vary between AMI patients was 117, 107, 86, 61, 58, 52, 46, 44,  34 kDa. Non immunogenic proteins were 97, 91, 23, 19, 9, 5 and 4 kDa. Protein 61 kDa react to all of patient’s serum. It was concluded, C. pneumoniae have protein fractions 117, 107, 97, 91, 86, 61, 58, 52, 46, 44, 34, 23, 19, 9, 5, and 4kDa. Immunogenic proteins vary between AMI patients was 117, 107, 86, 61, 58, 52, 46, 44, 34 kDa, and 61 kDa was the  immunodominant protein. The result proved C. pneumoniae as causative agent of atherosclerosis and acute myocardial infarction, in Indonesia particularly. Key words:C. pneumoniae, immunogenic, AMI